Construção empírica e validação de um instrumento de avaliação global de saúde mental - Geilsa Soraia Cavalcanti Valente; Elaine Antunes Cortez; Carlos Alberto da Cruz Sequeira (Sociedade Brasileira de Enfermagem em Feridas e Estética, 2019)
Com a realização deste estudo, pretendeu-se elaborar e validar o construto e a confi abilidade de uma escala de avaliação global do nível de saúde mental. A escala foi construída a partir da busca on-line e localização de 63 modelos de avaliação em saúde mental e posteriormente aplicada em 266 pessoas dos diversos grupos humanos. O processo envolveu a validação do conteúdo por 25 especialistas, participantes do Grupo Internacional[...] Palavras-chave: Saúde mental; Psicometría; Avaliação de Programas e Instrumentos de Pesquisa. ABsTRAcT In this study, it was intended to develop and validate the construct and the reliability of a global rating scale of mental health level. The scale was constructed from the online search and location of 63 evaluation models in mental health and later applied to 266 people of various human groups. The process involved the validation of content by 25 experts, participants of the International Research Group on Mental Health Nursing, pilot testing, reliability of measurement using the Cronbach's alpha coeffi cient and factor analysis. Adequate Cronbach coeffi cients were obtained in three dimensions and the factor analysis confi rmed the dimensions of scale[...] Keywords: Mental Health; Psychometrics; Evaluation Program and Research Instruments.